Macrophage-polarizing stimuli differentially modulate the inflammatory profile induced by the secreted phospholipase A2 group IA in human lung macrophages. (February 2021) - Ferrara, Anne Lise; Galdiero, Maria Rosaria; Fiorelli, Alfonso; Cristinziano, Leonardo; Granata, Francescopaolo; Marone, Giancarlo; Crescenzo, Rosa Maria Di; Braile, Mariantonia; Marcella, Simone; Modestino, Luca; Varricchi, Gilda; Spadaro, Giuseppe; et al.
Highlights: svGIA induced the release of inflammatory cytokines, chemokines and angiogenic factors in HLMs. IL-4 and IL-10 inhibited the release of TNF-α, IL-6, CXCL8, CCL1 and ANGPT1 induced by LPS and svGIA. IFN-γ reduced IL-10, VEGF-A and ANGPT1 but increased CCL1 release induced by LPS- and svGIA. NECA reduced TNF-α and CCL1 release but increased VEGF-A release by LPS and svGIA. IL-10 and NECA increased LPS- and svGIA-induced VEGF-A release. Abstract: In this study we investigated the effects of snake venom Group IA secreted phospholipase A2 ( sv GIA) on the release of inflammatory and angiogenic mediators from human lung macrophages (HLMs). HLMs were incubated with lipopolysaccharide (LPS) or sv GIA with or without macrophage-polarizing stimuli (IL-4, IL-10, IFN-γ or the adenosine analogue NECA). M2-polarizing cytokines (IL-4 and IL-10) inhibited TNF-α, IL-6, IL-12, IL-1β, CXCL8 and CCL1 release induced by both LPS and sv GIA. IL-4 inhibited also the release of IL-10. IFN-γ reduced IL-10 and IL-12 and increased CCL1 release by both the LPS and sv GIA-stimulated HLMs, conversely IFN-γ reduced IL-1β only by sv GIA-stimulated HLMs. In addition, IFNγ promoted TNF-α and IL-6 release from sv GIA-stimulated HLMs to a greater extent than LPS. NECA inhibited TNF-α and IL-12 but promoted IL-10 release from LPS-stimulated HLMs according to the well-known effect of adenosine in down-regulating M1 activation. By contrast NECA reduced TNF-α, IL-10, CCL1 and IL-1β release from sv GIA-activated HLM. IL-10 and NECA increased both LPS- and sv GIA-induced vascular endothelial growth factor A (VEGF-A) release. By contrast, IL-10 reduced angiopoietin-1 (ANGPT1) production from activated HLMs. IFN-γ and IL-4 reduced VEGF-A and ANGPT1 release from both LPS- and sv GIA-activated HLMs. Moreover, IL-10 inhibited LPS-induced ANGPT2 production. In conclusion, we demonstrated a fine-tuning modulation of sv GIA-activated HLMs differentially exerted by the classical macrophage-polarizing cytokines.